2019-2023 Corporate Plan (Australian Sports Commission, 2019)
The Australian Sports Commission Board is pleased to present the Corporate Plan 2019-23, which covers the period of 2019-20 to 2022-23. It has been developed in accordance with the requirements under paragraph 35(1)(b) of the Public Governance, Performance and Accountability Act 2013 and paragraphs 23 and 25 of the Australian Sports Commission Act 1989. This Corporate Plan has been developed to meet the requirements of the Corporate Plan and Annual Operational Plan as required under paragraph 26 of the Australian Sports Commission Act 1989. ... Our Corporate Plan 2019-2023 aligns with Sport 2030 — the Australian Government`s strategic sports plan launched in August 2018. We are delivering three key outcomes: - GETTING MORE AUSTRALIANS MOVING MORE OFTEN, - BUILDING THE CAPABILITY OF SPORT TO CREATE A ROBUST, CONNECTED INDUSTRY, - CREATING NATIONAL PRIDE AND INSPIRATION THROUGH INTERNATIONAL SPORTING SUCCESS.